How does Spinal Mobility Affect Balance and Postural Control in Patients with Ankylosing Spondylitis? A Cross-Sectional Study - Balim, Hatice; Unver, Bayram; Sevik, Kevser; Unver, Fatma (Aktuelle Rheumatologie, 2022)
Purpose Alterations in spinal mobility lead to impaired postural control and balance, an increased risk of falls and a decrease in quality of life. The purposes of this study were to investigate the relationship between spinal mobility, postural control and balance and to compare spinal mobility and balance with a view to disease severity in patients with ankylosing spondylitis (AS).Methods 137 patients with AS were divided into 2 groups by tragus-to-wall distance (TWD): (Group I=mild AS, n=51), (Group II=moderate AS, n=86). Balance was assessed with the Single-Leg Balance Test, the Timed Up and Go Test (TUG) and the Berg Balance Scale (BBS). Spinal mobility was measured by BASMI Index [TWD, cervical rotation (CR), Modified Schober Test (MST), lumbar lateral flexion (LLF), intermalleolar distance (IMD) and thoracic expansion (TE)] and was compared between the groups. The association with balance was investigated.Results Spinal mobility and BBS scores in Group II were worse than in Group I (p<0.05). Static balance and TUG of the groups were similar (p>0.05). Dynamic balance was weakly correlated with MST, LLF and IMM and moderately correlated with CR, TE and BASMI. Static balance was weakly correlated with spinal mobility (p<0.05). There was no correlation between TWD and any balance domains (p>0.05).Conclusions In patients with AS, spinal mobility and dynamic balance worsen as the disease progresses, whereas static balance does not change. Such changes in mobility and balance can negatively affect patients’ participation in daily life and increase their risk of falls. Therefore, detailed evaluation of balance, balance training and fall prevention approaches need to be implemented in the rehabilitation programs of patients with AS.
Keywords: ankylosing spondylitis; falls; balance; mobility; postural balance